Immunopathology of experimental autoallergic sialadenitis in C3H/He mice. - Hayashi, Y (1989)
We have shown that autoallergic sialadenitis develops in C3H/He (H-2k) mice thymectomized 3 days after birth and then immunized at 4 or 6 weeks of age with a homogenate of the submandibular salivary gland emulsified in Freund's complete adjuvant. Significant inflammatory changes did not develop in other inbred strains, such as BALB/c (H-2d), and C57BL/6 (H-2b) mice, examined by the same experimental protocol, or in the control groups, i.e. animals thymectomized at day 3 but not immunized, and animals not thymectomized but immunized. The cellular infiltrates observed in C3H/He mice with sialadenitis consisted of small and medium-sized lymophocytes stained with anti-Thy-1.2 antibody (the major proportion positive with anti-L3T4 and the lesser, with anti-Lyt 2). Anti-salivary duct antibodies were detected frequently in the sera of the C3H/He mice with sialadenitis.